The cost-effectiveness of government actions to reduce sodium intake through salt substitutes in Vietnam - Colman Taylor; Annet C. Hoek; Irene Deltetto; Adrian Peacock; Do Thi Phuong Ha; Michael Sieburg; Dolly Hoang; Kathy Trieu; Laura K. Cobb; Stephen Jan; Jacqui Webster (BMC, 2021)
Abstract Background Dietary sodium reduction is recommended to reduce the burden of cardiovascular disease. In Vietnam food products including salt, fish sauce and bot canh contribute to ~ 70% of dietary sodium intake. Reduced sodium versions of these products can be produced by replacing some of the sodium chloride with potassium chloride. We aimed to assess the cost-effectiveness of three alternative approaches to introducing reduced sodium products onto the market with a view to lowering population sodium intake in Vietnam. Methods The three salt substitution strategies included voluntary, subsidised and regulatory approaches targeting salt, fish sauce and bot canh products. Costs were modelled using the WHO-CHOICE methodology. A Markov cohort model was developed to evaluate the cost-effectiveness of each strategy versus no intervention from the government perspective. The model linked each intervention strategy to assumed changes in levels of sodium intake and then to systolic blood pressure. Changes in SBP were linked to a probability of ischaemic heart disease or stroke. The model followed people over their lifetime to assess average costs and quality adjusted life years (QALYs) gained for each strategy. Results The voluntary salt substitution strategy was assumed to require no investment by government. Following ramp up (years 6+), the average annual costs for the subsidised and regulatory strategies were 21,808,968,902 ₫ (US$ 977,354) and 12,949,953,247 ₫ (US$ 580,410) respectively. Relative to no intervention, all three salt substitution strategies were found to be cost-effective. Cost savings were driven by reductions in strokes (32,595; 768,384; 2,366,480) and ischaemic heart disease (IHD) events (22,830; 537,157; 1,648,590) for the voluntary, subsidised & regulatory strategies, respectively. The voluntary strategy was least cost-effective (− 3445 ₫ US$ -0.15; 0.009 QALYs gained) followed by the subsidised strategy (− 43,189 ₫ US$ -1.86; 0.022 QALYs gained) and the regulatory strategy delivered the highest cost savings and health gains (− 243,530 ₫ US$ -10.49; 0.074 QALYs gained). Conclusion This research shows that all three modelled salt substitution strategies would be good value for money relative to no intervention in Vietnam. The subsidised alternative would require the highest level of government investment; however the implementation costs will be exceeded by healthcare savings assuming a reasonable time horizon is considered.